CORPORATE ENTREPRENEURSHIP IN DIGITAL ERA SEBAGAI PENDORONG UTAMA INOVASI DAN PERTUMBUHAN DALAM MENGEMBANGKAN ORGANISASI: STUDI KASUS DI GO-JEK - Fat'Chatus Chanifa Jikhan; Ratih Purbasari; Margo Purnomo (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
As one of the tech companies in Indonesia, Gojek contributes to building innovation in the industry in this digital era through the principles, culture, and values embedded in its organisation. All of that is inseparable from the use of technology which is the main driving factor driving its business. In this research, the author aims to analyse Corporate Entrepreneurship in Gojek technology company in the digital era by using descriptive qualitative method through secondary data through literature study.